Postmodernism as World View in the Golden Compass Movie by Chris Weitz: The Application of Lucien Goldman’s Genetic Structuralism Theory - McFulvia HY (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2018)
This research clarifies Postmodernism as World View in The Golden Compass movie by Chris Weitz. The researcher applies Descriptive qualitative methods. An analysis is done by applying the Genetic structuralism theory by Lucien Goldmann to find the authors’ world view as a Trans-individual subject in the movie which can be categorized as a postmodern work. The research found that: World View in The Golden Compass movie can be divided into three parts; (1) The World View of God; the existence of divine reality is represented through Lyra Belacqua, Pantalaimon, and Lord Asriel’s research. (2) In the World View of Human, there is a reaction against to modernism system done by Lyra Belacqua, The Gyptian, and The Witches, in which the resistance is based on the concept of Egalitarianismas efforts to realize postmodernism ideals. (3) In the World View of Nature, there is an Anthropomorphism concept represented by the relationship between Lyra Belacqua and Iorek Byrnison characters. So, it may be concluded that the movie is one of the efforts by authors, Phillip Pullman and Chris Weitz to create history and to change the social structure by using their ideology and aspirations as the part of Trans-individual subject.